A constituição da identidade do diretor de escola de educação básica negro: articulações entre a identidade étnico-racial e a identidade profissional - Ferreira, Maria Angélica Chagas (2019)
This research is based on the study of a social phenomenon within the school that discusses, investigates and analyzes the relations between the identity trajectory of the black school principal, when in the process of assuming a position of leadership in municipal schools in the city of São Paulo, teaching and professional knowledge built and under construction along this route (PIMENTA, 1997; DUBAR, 1997, 2006, 2012). We aim to know a little about the professional and personal history of some black school principals during the teaching period and, currently, as managers, when talking about the reality of the school, the difficulties of the profession, the school and training history, the family and the The process of ethnic-racial construction seeks to have a panorama of the visibility of blacks in charge of leadership, and whether their racial identity is perceived negatively when measuring their professional competence. We have traveled a path in search of relevant definitions such as school administration and school principal in current legislation such as Law 9394/96-LDBEN. The authors Santos. B (2003), Ribeiro. J (1982), Paro (2011, 2015), Heller (1970), Gramsci (1968, 2001) structure the initial theoretical basis of research, assisting in the perspective of democratic management. Admission to the post is via public tender, and since 2013 there is affirmative action policy legislation for public service entry in the city. In this sense, we also study important concepts such as identity, prejudice, brand prejudice, racism and affirmative action policies. The authors Gomes (1995, 2017), Hall (2013, 2014), Silva (2014), Bento (2005), Ribeiro (2017), Almeida (2019), Fonseca (2009), Nogueira (1985, 1998) help us to understand these concepts in the reality of schools. We use the oral history method, with the testimonial, interview and script techniques, with the authors Nogueira (1973), Thompson (1992), Ezpeleta and Rockwell (1986), and Thiollent and Michael (1984), who give us the basis. for methodological organization. We organized an interview script, which was held in schools with black school principals, some freshmen and some older in the role. We interviewed male and female principals in their daily lives, we know the realities of schools and people in vulnerable situations who see a bridge in the school for better living conditions. For data analysis and categorization, our reference was Bardin (2011) and Minayo (2014). We used three categories that helped us better understand the context that we propose to deepen, they are: childhood, family and school; education, teaching and school management; and ethnic identity: being black and school principal. Our conclusion is that despite the individual and institutional racism experienced by school principals, they try to overcome difficulties and develop relevant work for the community in which they operate, without victimizing themselves. They fight daily to be recognized as school principals, in the meeting between reality and expectation, they work and seek strategies that help them in the challenges they find in this social place they occupy. Ethnic-racial identity becomes an instrument of struggle, mainly to legitimize fundamental elements of constitution of their professional identity.